2013
DOI: 10.3109/02713683.2013.790977
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Changes Produced in Response to Long-Term Overnight Orthokeratology

Abstract: A long period of OK reduces ACD and AL and changes PRCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…González-Mesa et al reported changes in the axial length and in the anterior chamber depth in young adult subjects with stable myopia corrected with orthokeratology [32]. These changes reverted after lens discontinuation and their data are also in the range of 0.1-0.15 mm as presented in our subjects.…”
Section: Discussionsupporting
confidence: 69%
“…González-Mesa et al reported changes in the axial length and in the anterior chamber depth in young adult subjects with stable myopia corrected with orthokeratology [32]. These changes reverted after lens discontinuation and their data are also in the range of 0.1-0.15 mm as presented in our subjects.…”
Section: Discussionsupporting
confidence: 69%
“…The OK lens wearers recruited were participants in a prior study conducted by our group and had been wearing Paragon-CRT lenses also for at least 3 years. 7,29 All subjects were whites.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesize that the failure of CXL to stabilize the corneal reshape effect by Ortho-K may be attributable to several possible reasons. Firstly, although it is yet conclusive that the effect of Ortho-K is mainly attributable to the corneal epithelial re-distribution [12][13][14] , other studies suggested the changes of corneal posterior surface www.nature.com/scientificreports www.nature.com/scientificreports/ flattening 15 , stromal thinning 16 and shorter anterior chamber depth after Ortho-K 17 . On the other hand, one study suggested that CXL might bring about structural changes in the stroma but these changes were mainly on the anterior 200 μm thick portion 18 .…”
Section: Discussionmentioning
confidence: 99%